Sustainable livestock policy of Colombia's national livestock producer organization (FEDEGAN) included information on improved pasture nutrition and methane emissions, which is informing livestock options in the development of the Government of Colombia's Nationally Appropriate Mitigation Action policy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The Colombian government developed mitigation options for a Nationally Appropriate Mitigation Action (NAMA) for livestock. FEDEGAN (Colombia's livestock federation) implemented a sustainable livestock strategy targeting 50,000 ha of degraded pastures. The NAMA and strategy were both informed by a model validation and data on livestock feeding strategies from CCAFS/CIAT.